2017
DOI: 10.21767/1791-809x.1000516
|View full text |Cite
|
Sign up to set email alerts
|

Practice of Labour Pain Management Methods and Associated Factors among Skilled Attendants Working at General Hospitals in Tigray Region, North Ethiopia: Hospital Based Cross-Sectional Study Design

Abstract: Introduction: Labour pain is the most severe pain that a woman ever has to face. Pain relief in childbirth is subject to many social and cultural modifiers, which continue to change. Delivery of the infant into the arms of a conscious and pain-free mother is the most exciting and rewarding moment in maternal care services. Developed nation give emphasis on continuous labour support, But in developing country pain is neglected especially managing labor pain. In a country like Ethiopia with low institutional del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
29
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(55 citation statements)
references
References 10 publications
(15 reference statements)
11
29
5
Order By: Relevance
“…The present study showed that 45.8% of obstetric caregivers had inadequate knowledge about labour pain relief methods. Our finding is lower than the findings reported from Tigray, Ethiopia (60.1%) and Ibadan, Nigeria (66.7%), respectively [13,17]. This difference might be explained in terms of difference in study setting and socio-demographic characteristics of study participants.…”
Section: Knowledge Of Obstetric Caregivers Towards Labour Pain Reliefcontrasting
confidence: 90%
See 4 more Smart Citations
“…The present study showed that 45.8% of obstetric caregivers had inadequate knowledge about labour pain relief methods. Our finding is lower than the findings reported from Tigray, Ethiopia (60.1%) and Ibadan, Nigeria (66.7%), respectively [13,17]. This difference might be explained in terms of difference in study setting and socio-demographic characteristics of study participants.…”
Section: Knowledge Of Obstetric Caregivers Towards Labour Pain Reliefcontrasting
confidence: 90%
“…The current study showed that the overall use of labour pain relief methods among obstetric caregivers was reported to be 34.4% (30.4% non-pharmacological and 8.4% pharmacological) methods, respectively. This finding is inconsistent with earlier studies' findings from different parts of Ethiopia: Tigray, 43.3% [13], Addis Ababa, 47.5% [19] and Amhara, 40.1% [14]. The reasons might be the preceding studies were conducted in public hospitals where better knowledge of labour pain relief methods and drug availability are potentially high.…”
Section: Use Of Labour Pain Relief Methods Among Obstetric Caregiverscontrasting
confidence: 75%
See 3 more Smart Citations